Ð¡Ñ‚Ñ€ÑƒÐºÑ‚ÑƒÑ€Ð½Ð¾-Ñ„ÑƒÐ½ÐºÑ†Ñ–Ð¾Ð½Ð°Ð»ÑŒÐ½Ð¸Ð¹ ÑÑ‚Ð°Ð½ Ð³ÐµÐ¼Ð°Ñ‚Ð¾ÐµÐ½Ñ†ÐµÑ„Ð°Ð»Ñ–Ñ‡Ð½Ð¾Ð³Ð¾ Ð±Ð°Ñ€â€™Ñ”Ñ€Ð° Ð¿Ñ€Ð¸ Ñ€Ð¸Ñ‚Ð¼Ñ–Ñ‡Ð½Ð¸Ñ… Ñ‚Ð° Ð±ÐµÐ·Ð¿ÐµÑ€ÐµÑ€Ð²Ð½Ð¸Ñ… Ð³Ñ–Ð¿Ð¾Ñ‚ÐµÑ€Ð¼Ñ–Ñ‡Ð½Ð¸Ñ… Ð²Ð¿Ð»Ð¸Ð²Ð°Ñ… Ð½Ð° Ð¾Ñ€Ð³Ð°Ð½Ñ–Ð·Ð¼ Ñ‰ÑƒÑ€Ñ–Ð² - Marchenko, V. S.; Babiychuk, G. A.; Marchenko, L. N. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
There was studied functional architecture of blood brain barrier (BBB) of rat’s neocortex and hypothalamus at hypothermia using the methods of determining the transport of neurotransmitters, electron microscopy and morphometry. It has been shown that continuous and rhythmically organized cold effects cause mono-directional alterations of linear morphometric parameters and principally different fractal peculiarities in structural and functional pattern of BBB elements. At continuous cold effect for 120 min the fractal dimension (D) of BBB elements of the studied brain structures changes synchronously and frequently makes ~1.5 (structural organization is in the zone of discordant rearrangements). Under rhythmic hypothermic effects the fractal dimension for BBB of anterior hypothalamus basically changes, but it remains in a persistent area (D~1.3). Under these conditions the BBB permeability significantly increases for neurotransmitters, that may determined the therapeutic effects of hypothermia.